Perselisihan Waris dan Validitas Surat Keterangan Hibah: Kajian Hukum dalam Penyelesaian Sengketa - Akbar Hidayatullah Daud; Agung Prayuda Yahya; Muhammad Khairun Kurniawan Kadir; Nurul Fazri Elfikri; Ramadhan Usman; Janwar Hippy (Journal of Law, Human Rights, Immigration, and Corrections, 2025)
Inheritance land grant disputes often arise in the Indonesian judiciary, especially regarding the validity of grants that do not use notarial deeds. This study aims to analyze the validity of the grant certificate (SKH) in the transfer of rights to undivided land inheritance and its impacts. The research method used is normative law with a legislation approach and case approach, specifically analyzing Manado High Court Decision Number 32/PDT/2024/PT MND. Results show that land grants not made by notarial deeds violate Article 1682 of the Civil Code, making them legally invalid and unusable as a basis for land registration. Registration of the transfer of rights to undivided inherited land is also not possible because the land remains an inheritance boedel owned collectively by all heirs. Registering the transfer of rights to undivided inherited land requires valid legal documents and must comply with applicable laws to ensure legal certainty for concerned parties.